Integral calculus - Montero-Galliquez, Thelma C.; Gaquing, Jr., Napoleon A.; Lopez-Conde, Rosie C.; Abao, Zenon R. (Quezon City : C & E PUBLISHING, INC., 2011)
This book is intended for a course on integral calculus. Together with the book on differential calculus, it is designed as a second course in calculus for science and engineering students.
Chapter 1. Integration -- Chapter 2. Trigonometric, logarithmic, and exponential functions -- Chapter 3. Techniques of integration -- Chapter 4. Improper integrals -- Chapter 5. Parametric equations and applications -- Chapter 6. Polar coordinates and applications -- Chapter 7. Applications of integration -- Chapter 8. Numerical integration -- Chapter 9. Sequences and series -- Chapter 10. Multiple integration.
Includes bibliographical references and indexes.
Keywords: INTEGRAL CALCULUS